Perencanaan Strategis Sistem Informasi dengan Metodologi Ward and Peppard dan AHP SMK Ma’arif NU 1 Ajibarang - Atipa Muji (STEKOM PRESS, 2021)
As an old educational institution, SMK Ma'arif NU 1 Ajibarang is growing rapidly, however it has not implemented Information Systems and Information Technology optimally in its business processes and does not yet have an Information Systems strategic planning portfolio. This is deemed necessary in making a strategic information system, in order to provide superiority in business competition. Information system strategic planning is one of the keys in implementing information systems and information technology in business activities. Strategic planning in this study uses themethod Ward and Peppard to compile an information system strategic plan at SMK Ma'aif NU 1 Ajibarang and AHP to determine the application roadmap. The results of this analysis define the information system strategic planning company in the form of an information system business strategy, information system management strategy and information technology, information system strategy, information system recommendations, future applications and implementation plans.